Good Practice in Trade Facilitation : Lessons from Tunisia - Alavi, Hamid (World Bank, Washington, DC, 2012)
Although trade liberalization can create jobs and raise incomes, these benefits can easily be undermined if trade transactions involve excessive costs and delays-reducing a country's export competitiveness. Trade facilitation efforts aim to reduce such costs and delays by simplifying trade procedures and document flows, modernizing customs and port systems, promoting quality and safety standards, and improving trade logistics. In recent years several countries have used information and communications technology to achieve one or more of these goals. Tunisia provides a good example of stakeholders coming together to simplify trade procedures and automate documentation and customs requirements. In fact, it is the first country in the Middle East and North Africa that has succeeded in applying information and communications technology to the entire range of trade documents. When other countries in the region (such as Morocco) have used such technology, they have focused on customs and ports, overlooking other practices and procedures that impose transactions costs on trade activities. This note summarizes the context and challenges, key initiatives, impact, and success factors of Tunisia's efforts.